Visualizing identity: linguistic landscapes and ethnolinguistic signage in indonesian multicultural neighborhoods - Heratul Aini (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Indonesia’s multicultural neighborhoods such as Glodok, Pecinan, Kampung Arab, and Kampung Bugis demonstrate how public signage embodies not only communication but also the negotiation of identity and power in urban spaces. Objective: The purpose of this research is to examine how ethnolinguistic visibility, cultural symbolism, and power relations are materialized in the linguistic landscapes of Indonesian cities. Method: The study employed a qualitative, multi-site design combining photographic documentation, semiotic interpretation, and critical discourse analysis across selected ethnic enclaves. Results: The findings reveal, first, that Indonesian dominates official signage while ethnic languages often remain hidden or minimized; second, that cultural symbolism—such as Chinese red-and-gold motifs or Arabic calligraphy—functions as a substitute for restricted linguistic expression; third, that bilingual or multilingual signage reflects regulated diversity where minority languages are acknowledged but subordinated under state-sanctioned hierarchies. Implication: These results imply that linguistic landscapes are powerful semiotic terrains that simultaneously reproduce and challenge dominant ideologies, providing insights for inclusive language policy, heritage preservation, and urban cultural planning. Novelty: This study shows how linguistic landscapes in multicultural urban enclaves materialize the tension between state-dominant language ideologies and the symbolic assertion of minority identities through regulated visibility and semiotic substitution.